Reviewing the Role of the Efferent Vestibular System in Motor and Vestibular Circuits - Mathews, Miranda A.; Camp, Aaron J.; Murray, Andrew J. (Frontiers in Physiology, 2017)
Efferent circuits within the nervous system carry nerve impulses from the central nervous system to sensory end organs. Vestibular efferents originate in the brainstem and terminate on hair cells and primary afferent fibers in the semicircular canals and otolith organs within the inner ear. The function of this efferent vestibular system (EVS) in vestibular and motor coordination though, has proven difficult to determine, and remains under debate. We consider current literature that implicate corollary discharge from the spinal cord through the efferent vestibular nucleus (EVN), and hint at a potential role in overall vestibular plasticity and compensation. Hypotheses range from differentiating between passive and active movements at the level of vestibular afferents, to EVS activation under specific behavioral and environmental contexts such as arousal, predation, and locomotion. In this review, we summarize current knowledge of EVS circuitry, its effects on vestibular hair cell and primary afferent activity, and discuss its potential functional roles.